Organic photodynamic nanoinhibitor for synergistic cancer therapy - Jiang, Yuyan (2020)
Despite its great potential in cancer treatment, photodynamic therapy (PDT) often exacerbates hypoxia and subsequently compromises its therapeutic efficacy. To overcome this issue, an organic photodynamic nanoinhibitor (OPNi) has been synthesized that has the additional ability to counteract carbonic anhydrase IX (CA‐IX), a molecular target in the hypoxia‐mediated signalling cascade. OPNi is composed of a metabolizable semiconducting polymer as the photosensitizer and a CA‐IX antagonist conjugated amphiphilic polymer as the matrix. This molecular structure allows OPNi not only to selectively bind CA‐IX positive cancer cells to facilitate its tumor accumulation but also to regulate the CA‐IX‐related pathway. The integration of CA‐IX inhibition into the targeted PDT process eventually has a synergistic effect, leading to superior antitumor efficacy over that of PDT alone, as well as the reduced probability of hypoxia‐induced cancer metastasis. This study thus proposes a molecular strategy to devise simple yet amplified photosensitizers to conquer the pitfalls of traditional PDT.